Analisis Penggunaan Aplikasi Whatsapp dalam Pembelajaran Jarak Jauh (PJJ) Pada Mata Pelajaran Bahasa Inggris Selama Wabah Covid-19 di MA Persatuan Islam Persis 69 Matraman Jakarta - Rizdki Elang Gumelar; Obay Jambari; Tatang Surya Atmaja (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2022)
In the midst of the Covid-19 outbreak that hit Indonesia, MA Persis 69 Matraman Jakarta is one of the schools that organize Teaching and Learning Activities with the Online Learning system. Online learning is considered the best solution in the midst of the epidemic condition that hit the country where this epidemic has become a frightening specter for many people. Online Learning is an alternative in the process of Teaching and Learning Activities. This is purposed to prevent the spread of Covid-19. In its implementation, teachers and students use the Whatsapp application as an online learning media during this pandemic. Whatsapp is one of the easiest and most commonly used applications. The Whatsapp application provides a group feature where all students can be involved in doing learning activities either by chatting, recording, or sending large video files. In this study, the research approach used is a qualitative approach, while the research methodology used is descriptive qualitative. The findings of this research showed that firstly, the learning process through the WA group as a whole can be said to have been in accordance with the learning steps, but in the future it still needs improvement so that learning becomes more optimal. Secondly, Learning Outcomes seen from the aspects initiated by Bloom's Taxonomy namely Cognitive, Affective and Psychomotor, the results obtained are not too far away different from face-to-face learning; it's just that for Psychomotor when this online leraning looks far, very bad. Lastly, Supporting and inhibiting factors learning include cheap learning costs and easily accessible learning resources being the main supporting factors, while the equipment is expensive for students who are economically disadvantaged and the poor internet connection in certain areas is an inhibiting factor in this online learning